Risk analysis for prevention of hazardous situations in petroleum and natural gas engineering - Matanovic, Davorin, 1949-; Gaurina-Medimurec, Nedilijka, 1957-; Simon, Katarina, 1962- (Advances in environmental engineering and green technologies (AEEGT) book series., 2014)
"This book explains the potential hazards of petroleum engineering activities, emphasizing risk assessments in drilling, completion, and production, and the gathering, transportation, and storage of hydrocarbons"--